Comparison of dissolution profile of extended-release oral dosage forms - two one-sided equivalence test (Brazilian Journal of Pharmaceutical Sciences, 2013)
The aim of this work is to present the two one-sided test (TOST) as an alternative approach to compare dissolution profiles of extended-release dosage forms. The dissolution profiles of oxycodone extended-release tablets containing 10 mg, 20 mg and 40 mg (reference and generic) were evaluated according to the requirements described in United States Pharmacopeia. These dissolution profiles were compared using the conventional similarity factor (f2) and the proposed TOST as an equivalence test. TOST is a simple and alternative approach to compare dissolution profiles of extended-release dosage forms. It allows us to identify the time-point (or time-points) that did not show similarity. We concluded that the two one-sided test performed at a significance level of 5% and defined as D = 10 showed results comparable to those obtained by the conventional similarity factor (f2).